2014
DOI: 10.1002/lt.23947
|View full text |Cite
|
Sign up to set email alerts
|

Ketanserin, a serotonin 2A receptor antagonist, alleviates ischemia-related biliary fibrosis following donation after cardiac death liver transplantation in rats

Abstract: Biliary fibrosis is a major complication after donation after cardiac death (DCD) liver transplantation. In this process, the roles of serotonin [5-hydroxytryptamine (5-HT)] and the 5-HT2A receptor subtype are still unknown. In this study, we analyzed markers of portal fibroblast (PF)/myofibroblast (MF) transdifferentiation such as transforming growth factor b1 (TGF-b1), phosphorylated smad2/3, a-smooth muscle actin (a-SMA), collagen I, and collagen III in a primary culture system of PFs after the administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
2
7
1
Order By: Relevance
“…Several studies have suggested anxiety-like behavior to be most often than not accompanied by protein expressional changes in 5HT2A and 5HT1A receptors in mice hippocampi [40, 46, 47]. Our western blot and immunofluorescence labeling results showed significant increment in the expression level of 5HT1A receptor after PTSD model establishment.…”
Section: Discussionsupporting
confidence: 61%
“…Several studies have suggested anxiety-like behavior to be most often than not accompanied by protein expressional changes in 5HT2A and 5HT1A receptors in mice hippocampi [40, 46, 47]. Our western blot and immunofluorescence labeling results showed significant increment in the expression level of 5HT1A receptor after PTSD model establishment.…”
Section: Discussionsupporting
confidence: 61%
“…Having low fibroblasts and increased proportion of myofibroblasts supports our findings of impaired re-epithelialization with ketanserin and fluoxetine administration. Our results conflict with a previous study that suggests systemic ketanserin administration causes down regulation of α-SMA expression in portal fibroblasts pre-treated with serotonin [ 40 ]. However, this study evaluated the mRNA and protein expression of cultured portal fibroblasts, while our observation was based on quantifying α-SMA-positive cells using skin tissue immunostaining.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, it is possible that the increased wound area and impaired epithelialization following ketanserin treatment is due to the impairment of the inflammatory response. Our results showing suppression of fibroblast and keratinocyte proliferation with ketanserin treatment also support previous studies indicating that ketanserin reduces fibroblast proliferation and induce fibrosis in the liver [ 40 ], whereas it is also documented that activation of 5HTR2A signaling promotes fibrosis in various other tissues [ 16 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…Activation of a chronic inflammation system can cause endothelial cells to secrete a variety of cytokines, chemokines, and plasminogen activator inhibitor type 1 (PAI-1), thereby reducing the fibrinolytic activity and leading to fibrous adhesion between perirenal fat and the renal capsule (17,18). In addition, serotonin [5-hydroxytryptamine (5-HT)], considered as fibrosis-related growth factor which is highly expressed in renal cell carcinoma contributes to APF (19,20). These paracrine mechanisms may partially explain why the probability of APF in benign renal tumors was lower than that in malignant tumors in our study.…”
Section: Discussionmentioning
confidence: 99%